The South Africa-Sweden University Forum (SASUF) - Sven Botha; Helin Bäckman Kartal (The Thinker)
Science diplomacy has been an endeavoured area of cooperation between Sweden and South Africa despite Sweden’s reluctance to practice science diplomacy. However, the introduction of the South Africa-Sweden University Forum (SASUF) in 2017 remains an underexplored phenomenon of knowledge diplomacy. Using Knight’s five characteristics of knowledge diplomacy (focus on higher education, research, and innovation; diversity of actors and partners; recognition of different needs and the collective use of resources; reciprocity; and the building and strengthening of relations between states), this paper argues that SASUF is an essential frontier for knowledge diplomacy in the context of South Africa-Sweden relations. The employment of Knight’s framework finds that SASUF can indeed be classified as an example of knowledge diplomacy. In conclusion, a new research agenda on knowledge diplomacy within the context of South Africa-Sweden relations is proposed.